2018
DOI: 10.1590/1678-4685-gmb-2017-0272
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization of the NRAMP gene family in Phaseolus vulgaris provides insights into functional implications during common bean development

Abstract: Transporter proteins play an essential role in the uptake, trafficking and storage of metals in plant tissues. The Natural Resistance-Associated Macrophage Protein (NRAMP) family plays an essential role in divalent metal transport. We conducted bioinformatics approaches to identify seven NRAMP genes in the Phaseolus vulgaris genome, investigated their phylogenetic relation, and performed transmembrane domain and gene/protein structure analyses. We found that the NRAMP gene family forms two distinct groups. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 77 publications
3
16
0
Order By: Relevance
“…However, there is a lack of detailed information about this family in peanuts. In this study, 15 NRAMP genes were identified from the peanut genome, which is the largest among reported plant species, including Arabidopsis (6) [ 11 ], rice (7) [ 42 ], soybean (13) [ 43 ], common bean (7) [ 44 ], potato ( Solanum tuberosum , 5) [ 45 ], tea plant ( Camellia sinensis , 11) [ 46 ], cacao ( Theobroma cacao , 5) [ 47 ], and Spirodela polyrhiza (3) [ 48 ]. A large number of genes in the peanut genome have been reported in the gene families of metal tolerance proteins [ 49 ], zinc/iron-regulated transporter-like proteins [ 50 ], and oligopeptide transporters [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a lack of detailed information about this family in peanuts. In this study, 15 NRAMP genes were identified from the peanut genome, which is the largest among reported plant species, including Arabidopsis (6) [ 11 ], rice (7) [ 42 ], soybean (13) [ 43 ], common bean (7) [ 44 ], potato ( Solanum tuberosum , 5) [ 45 ], tea plant ( Camellia sinensis , 11) [ 46 ], cacao ( Theobroma cacao , 5) [ 47 ], and Spirodela polyrhiza (3) [ 48 ]. A large number of genes in the peanut genome have been reported in the gene families of metal tolerance proteins [ 49 ], zinc/iron-regulated transporter-like proteins [ 50 ], and oligopeptide transporters [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these genes, four other genes belonging to the NRAMP (natural resistance-associated macrophage protein) family, NRAMP1, NRAMP3, NRAMP4, and NRAMP5, have been described to be involved in Zn sequestration in the vacuole of leaf cells. These transporters use the transmembrane proton gradient to facilitate the transport of a broad range of divalent cations toward the cytosol [166]. In N. caerulescens, NRAMP1 and NRAMP5 were found to be highly expressed in the shoots specifically [167,168].…”
Section: Zinc Sequestration In the Aboveground Part Of The Plantsmentioning
confidence: 99%
“…Phylogenetic analysis clustered all of their encoded proteins into two distinct subfamilies. The subcellular localization of proteins in the same subfamily was similar among Arabidopsis, rice, common bean, and soybean (Qin et al 2017;Mani and Sankaranarayanan 2018;Ishida et al 2018). Interestingly, all of the melon NRAMPs except CmNRAMP5 contained fewer motifs and had shorter amino acid sequences than their homologs in other plants.…”
Section: Discussionmentioning
confidence: 95%